Is There a Relationship Between Household Saving Behavior, Trust in Financial Institutions and Saving Attitudes in Contemporary Russia? - Kuzina, Olga; Moiseeva, Daria (Journal of Economic Sociology, 2024)
The paper examines household savings as one of the indicators of household financial fragility/resilience in Russia. The main goal is to reveal the relationship between people’s trust in financial institutions, their saving behavior and their savings attitudes. The study of financial fragility/resilience is important for the development of economic and social policies, especially in relation to those conditions upon which state can work. The study contributes to the existing literature by using Russian micro data and the inclusion of trust in institutions and savings attitudes among the covariates of household savings. The empirical basis of the study is cross-sectional data from all-Russian population surveys collected in 2009-2023. The financial resilience is low due to the fact that only about one third of Russians have savings which amount is rather small. The data also show high levels of distrust towards most socio-political and financial institutions. Based on the principal components method, two latent factors of trust were identified. The first one was related to trust in socio-political institutions, Sberbank and Bank of Russia, Deposit Insurance Agency (DIA) and state-owned banks, the second one included trust in all non-state financial institutions. Regression analysis showed that saving attitudes and both components of trust are positively correlated with savings. Associative rule learning method showed that even in presence of the positive attitude towards savings the most common non-random combinations of answers were lack of savings, distrust towards banks (with the exception of Sberbank), distrust to the Deposit Insurance Agency. Thus, distrust of socio-political and financial institutions is an obstacle to the increase in the amount of savings and financial resilience of Russian households.